Elucidating data analysis procedures in research reports on language education: an inquiry into writers? communicative resources - Lim, Jason Miin Hwa (International Journal of Social Science and Humanity(IJSSH), 2012)
Helping learners acquire the skills in writing research methods constitutes an important component in various programmes in tertiary education. One of the challenges encountered by novice writers in language education has to do with the elucidation of data analysis procedures in experimental research reports. Adopting a genre-based approach, this study analyses the rhetorical strategies and linguistic resources used for recounting and justifying the steps taken in analyzing data. Employing the Statistical Package for Social Sciences (SPSS), the researcher conducted a quantitative analysis of the rhetorical steps used by experienced writers in 32 experimental research reports published in eight reputed international refereed journals. Attention was directed to the determination of the degree to which the frequencies of the steps under investigation-focused headings differ from those under procedure-focused headings. A detailed qualitative analysis of the writers’ textual data was also conducted to identify the broad spectrum of language mechanisms employed in recounting and justifying the data analysis procedures. The findings have shed some light on what and how dissertation supervisors and instructors can possibly highlight while guiding second language writers to recount and justify data analysis procedures in experimental studies on language education.